DESAIN PERBAIKAN POSTUR KERJA OPERATOR MAINTENANCE PADA PT MININDO MENGGUNAKAN SOFTWARE SOLIDWORK DENGAN PENDEKATAN ANTROPOMETRI - Marulan Andivas; Dimaz Harits; Agus Hindarto Wibowo; Riandimas Nursava Putra (JURNAL PERANGKAT LUNAK, 2023)
When working on diesel engine repairs, operators at PT. Minindo mostly does its job by sitting on the machine it is working on. The operator's job analysis was carried out using the REBA method, based on the analysis a score of 11 was obtained which means that the risk is very high so that work methods are needed to be improved. The proposed improvement is to make a staircase design using Indonesian anthropometric data. The ladder design is made so that the operator does not have to be on top of the machine when working, because there is a risk of falling and musculoskeletal disorders Based on data processing, the height of the ladder is 137cm, the height of the top rung is 115cm, the width of the ladder is 177cm, the width of the steps is 20cm, the depth of storage for tools is 81cm, the width for storing tools is 47cm. The ladder is expected to reduce the risk of accidents, as well as improve the work posture of PT. Minindo. The stairs sizes obtained are then applied to Solidwork software.